Jinx - Wild, Margaret,Zeitz, Sophie (Hanser, 2003)
With the help of her understanding mother and a close friend, Jen eventually outgrows her nickname, Jinx, and deals with the deaths of two boys with whom she had been involved.
Keywords: Jugendbuch; Australian fiction; Novels in verse; Friendship; Interpersonal relations; Self-perception; Verlieben; Weibliche Jugend; Liebeskummer